2021
DOI: 10.1111/evo.14205
|View full text |Cite
|
Sign up to set email alerts
|

Demographic consequences of dispersal‐related trait shift in two recently diverged taxa of montane grasshoppers*

Abstract: Although the pervasiveness of intraspecific wing‐size polymorphism and transitions to flightlessness have long captivated biologists, the demographic outcomes of shifts in dispersal ability are not yet well understood and have been seldom studied at early stages of diversification. Here, we use genomic data to infer the consequences of dispersal‐related trait variation in the taxonomically controversial short‐winged (Chorthippus corsicus corsicus) and long‐winged (Chorthippus corsicus pascuorum) Corsican grass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 109 publications
(237 reference statements)
0
11
0
Order By: Relevance
“…Ortego et al. (2021) thus illustrate the links between dispersal traits and both microevolutionary and macroevolutionary processes (Figure 1; see also Harvey et al. 2019).…”
Section: Figurementioning
confidence: 91%
See 4 more Smart Citations
“…Ortego et al. (2021) thus illustrate the links between dispersal traits and both microevolutionary and macroevolutionary processes (Figure 1; see also Harvey et al. 2019).…”
Section: Figurementioning
confidence: 91%
“…In summary, Ortego et al. (2021) clearly demonstrated that shifts in dispersal‐associated traits can directly influence geographic structuring and intraspecific diversification in a topographically complex habitat. Increased rate of intraspecific diversification in the short‐winged lineages may ultimately lead to higher rates of speciation and interspecific diversification.…”
Section: Figurementioning
confidence: 96%
See 3 more Smart Citations